Defining the Locus of Dopaminergic Dysfunction in Schizophrenia: A Meta-analysis and Test of the Mesolimbic Hypothesis. (28th December 2017) - McCutcheon, Robert; Beck, Katherine; Jauhar, Sameer; Howes, Oliver D
Abstract: Background: Studies using positron emission tomography to image striatal dopamine function, have demonstrated that individuals with schizophrenia display increases in presynaptic function. Mesolimbic dysfunction specifically, has previously been suggested to underlie psychotic symptoms. This has not been directly tested in vivo, and the precise anatomical locus of dopamine dysfunction within the striatum remains unclear. The current article investigates the magnitude of dopaminergic abnormalities in individuals with schizophrenia, and determines how the magnitude of abnormality varies across functional subdivisions of the striatum. Methods: EMBASE, PsychINFO, and MEDLINE were searched from January 1, 1960, to December 1, 2016. Inclusion criteria were molecular imaging studies that had measured presynaptic striatal dopamine functioning. Effects sizes for whole striatum and functional subdivisions were calculated separately. The magnitude of difference between functional subdivisions in patients and controls was meta-analyzed. Results: Twenty-one eligible studies were identified, including 269 patients and 313 controls. Individuals with schizophrenia (Hedges' g = 0.68, P < .001) demonstrated elevated presynaptic dopamine functioning compared to controls. Seven studies examined functional subdivisions. These demonstrated significant increases in patients compared to controls in associative ( g = 0.73, P = .002) and sensorimotor ( g = 0.54, P = .005) regions, but not limbic ( g = 0.29, P = .09). The magnitude of the difference between associative and limbic subdivisions was significantly greater in patients compared to controls ( g = 0.39, P = .003). Conclusion: In individuals with schizophrenia dopaminergic dysfunction is greater in dorsal compared to limbic subdivisions of the striatum. This is inconsistent with the mesolimbic hypothesis and identifies the dorsal striatum as a target for novel treatment development.